Unlocking Opportunities for Shariah Business Units: A Prospectus for Post-2023 Dynamics - Pratama, Aditya (AL-FALAH : Journal of Islamic Economics, 2023)
Purpose: The Paper aim to explore what possibilities Shariah Business Units could hold the mandate of Law Islamic BankingDesign/Method/Approach: This study uses a descriptive analysis. It intensively Implemented a qualitative approach to obtain information and collected the data needed through relevant literatures and studies.Findings: This paper provide several recommendations such as a direct spinoff for the five SBU with the largest assets, combining BUS with an existing Islamic Bank, combining several SBU and then spinoff, and finally converting Conventional Bank which has SBU to become an Islamic Bank.Originality/Values:Â  This study's originality lies in its comprehensive analysis of the strategic implications and potential outcomes for Shariah Business Units (SBU) within conventional banks, considering a specific legal timeframe, multiple transition scenarios, and practical recommendations for stakeholders in the evolving landscape of Islamic banking.